2006
DOI: 10.1021/ja057451+
|View full text |Cite
|
Sign up to set email alerts
|

Excited-State Dynamics of Structurally Characterized [ReI(CO)3(phen)(HisX)]+ (X = 83, 109) Pseudomonas a eruginosa Azurins in Aqueous Solution

Abstract: The triplet metal-to-ligand charge transfer ((3)MLCT) dynamics of two structurally characterized Re(I)(CO)(3)(phen)(HisX)-modified (phen = 1,10-phenanthroline; X = 83, 109) Pseudomonas aeruginosa azurins have been investigated by picosecond time-resolved infrared (TRIR) spectroscopy in aqueous (D(2)O) solution. The (3)MLCT relaxation dynamics exhibited by the two Re(I)-azurins are very different from those of the sensitizer [Re(I)(CO)(3)(phen)(im)](+) (im = imidazole). Whereas the Re(I)(CO)(3) intramolecular v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(96 citation statements)
references
References 50 publications
4
91
1
Order By: Relevance
“…[1][2][3][4]25] As their detailed excitedstate characters are very sensitive to the medium, Re I complexes can serve as probes of the character and dynamics of the chromophore environment, which can be varied from simple solvents to polymers or protein binding sites. [4,10] Optical excitation of the {Re I (CO) 3 A C H T U N G T R E N N U N G (N,N)} chromophore into an MLCT excited state redistributes the electron density to {Re II (CO) 3 A C H T U N G T R E N N U N G (N,NC À )}. In response, the axial ligand X can perform various chemical functions, depending on whether it is an electron donor, electron acceptor, or an energy acceptor.…”
Section: A C H T U N G T R E N N U N G (Bpy)]mentioning
confidence: 99%
“…[1][2][3][4]25] As their detailed excitedstate characters are very sensitive to the medium, Re I complexes can serve as probes of the character and dynamics of the chromophore environment, which can be varied from simple solvents to polymers or protein binding sites. [4,10] Optical excitation of the {Re I (CO) 3 A C H T U N G T R E N N U N G (N,N)} chromophore into an MLCT excited state redistributes the electron density to {Re II (CO) 3 A C H T U N G T R E N N U N G (N,NC À )}. In response, the axial ligand X can perform various chemical functions, depending on whether it is an electron donor, electron acceptor, or an energy acceptor.…”
Section: A C H T U N G T R E N N U N G (Bpy)]mentioning
confidence: 99%
“…It will be demonstrated that the SO model accounts very well for absorption spectra, emission properties, and excited-state dynamics, some of its conclusions being qualitatively different from the spinfree approach. [Re(imH)(CO) 3 (phen)] + represents a broad class of Re I tricarbonyl-diimine complexes [21][22][23], which show very rich photophysics and photochemistry [10,14,15,24] and engage in a range of photonic applications such as photosensitizers and phototriggers of electron-transfer reactions [11,[25][26][27][28][29], photocatalysts of CO 2 reduction [30][31][32], phosphorescent labels and probes of biomolecules [33][34][35][36], sensors [37,38], molecular switches [39][40][41][42] and OLED emitters [43], or probes of ps-ns dynamics of solvents, proteins or supramolecular hosts [11,24,50,51,[63][64][65]. The chosen example [Re(imH)(CO) 3 (phen)] + [44] not only epitomizes the salient features of Re I carbonyl-diimine photophysics but also has a prominent position amongst Re-based photosensitizers because of its ability to trigger photoinduced electron transfer and relaxation dynamics in Re-labeled proteins [11,25,[44]…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, when the copper(I) oxidation rates are plotted against Cu-surface histidine distances, an excellent agreement with those predicted based on the standard distance-decay constant b of 1.1 Å −1 is observed, concluding the involvement of the metal-coordinated histidine in the electrontransfer. In another study, the 3 MLCT relaxation dynamics displayed by two structurally characterised mutants [Re(phen)(CO) 3 (HisX)]-Az (X = 83, 109) in D 2 O have been examined by picosecond time-resolved infrared spectroscopy [31]. A much slower medium relaxation has been ascribed to the reorientation of the solvent molecule and the structural reorganisation of the rhenium complex and the nearby polar amino acid residues.…”
Section: Protein Probesmentioning
confidence: 98%